Allmania janakiae (Amaranthaceae)—an interesting new species from Kerala, South India - Arya, Sindhu; Kumar, Venugopalan Nair Saradhamma Anil (Phytotaxa, 2024)
A new species of Allmania—Allmania janakiae—has been described from vegetational belts near the coastal areas of Kollam district of the state of Kerala. Floral traits like absence of bracteole, shape and length of bract, length of tepals, number of flowers per synflorescence, pollen morphology and lack of aril in the seed clearly delineates the new taxon from A. nodiflora and A. multiflora, the two species currently known from the genus. SEM images of seed and pollen along with colour photographs have been provided. The species status of the taxa has been confirmed using ITS gene.